Effectiveness of losartan on infrapatellar fat pad/synovial fibrosis and pain behavior in the monoiodoacetate-induced rat model of osteoarthritis pain - Sriwatananukulkit O. (2023)
Infrapatellar fat pad (IFP)/ synovial fibrosis is closely associated with the clinical symptoms of joint pain and stiffness, which contribute to locomotor restriction in osteoarthritis (OA) patients. Hence, this study was designed to gain insight on whether losartan, a selective angiotensin II type 1 receptor (AT1R) antagonist, has therapeutic benefit to reverse IFP/synovial fibrosis and secondarily to attenuate pain behavior. In male Wistar rats with monoiodoacetic acid (MIA)-induced IFP/synovial fibrosis, a possible role for increased AT1R expression in the pathogenesis of IFP/synovial fibrosis was assessed over an 8-week period. Pain behavior comprised static weight bearing and von Frey paw withdrawal thresholds (PWTs), which were assessed once or twice weekly, respectively. Groups of MIA-rats received oral losartan (30-mg/kg; n = 8 or 100-mg/kg; n = 9) or vehicle (n = 9) for 28-days according to a prevention protocol. Animals were euthanized on day 28 and various tissues (IFP/synovium, cartilage and lumbar dorsal root ganglia (DRGs)) were collected for histological, immunohistochemical and western blot analyses. Administration of once-daily losartan for 28-days dose-dependently attenuated the development of static weight bearing. This was accompanied by reduced IFP/synovial fibrosis and suppression of TGF-β1 expression. Chronic treatment of MIA-rats with losartan had an anti-fibrotic effect and it attenuated pain behavior in this animal model.